A Prospective Observational Comparative study Between qSOFA and SIRS Scores for Early Prediction of Sepsis Outcome in an Emergency Medicine Department , Kozhencherry, South Central Kerala,India - Rahul Rajeev; , J S Krishna Raj; Anu T R; Pratibha Dabas; Roshni; Seeja Sumedhan (Global Journal of Medicine and Public Health)
Background